Max and Grandma and Grampa Winky - Steel, Danielle; Rogers, Jacqueline, 1958- (New York, N.Y. : Delacorte Press, 1990)
Grampa, Mom, and Dad help seven-year-old Max deal with his feelings of sadness and loss following the death of his grandmother.
Keywords: Grandparents -- Fiction; Death -- Fiction